Adsorption Mechanism of Chitosan/Polyvinyl Alcohol (PVA) Hydrogels in Wastewater Treatment - Mohd Roslim, Mohd Iqbal (IRC, 2016)
The potential use of chitosan based exchangers or adsorbents on a large scale have been discovered in wastewater treatment to uproot substantial metal ions and dye removal. Polyvinyl alcohol (PVA) was grafted onto chitosan and chemically cross-linked to produce a hydrogel for the adsorption of lead (Pb (II)) ions. The hydrogels synthesized were different in terms of chitosan content ranging from 1 wt%, 2 wt% and 3 wt% in order to study its effect on lead adsorption. Higher dosages of chitosan in the hydrogel resulted in higher adsorption of lead as the 3 wt% hydrogel had the highest adsorption capacity with a removal yield of 97.82% of lead ions due to the availability of more nitrogen atoms for binding with the lead ions